Perkembangan Anak dalam Tinjauan Psikologi (Studi Kasus di Pondok Cilik Maktab Nubdzatul Bayan Pamekasan) - Imam Hanafi (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2022)
This research aims to examine the psychological  development of children in pesantren. It chooses Pondok Cilik Maktab Nubdzatul Bayan Pamekasan as case study. Analyzing this research , it uses naturalistic qualitative approach by a descriptive analysis. Its datas are collected by participant observation, depth interview, scale, and documentation. Then the datas are analyzed by Miles and Huberman models. The results show that there are two various psychological development of the childden in the pesantren. The first, is apropriate development that includes weight, behavior, skills of writing and reading. The children are able to adapt to rules by obeying the them, and memorize some prayings. The second is inaproriate development, for the example they are inaproriate with their weight, skills on speaking maduranesse language. Also, they tend to be atrouble maker, playing intensively, and hard to pray.